Behavioral management of exercise training in vascular headache patients: an investigation of exercise adherence and headache activity. - Fitterling, J M (1988)
A behavioral package was used to shape and maintain the adherence of 5 subjects with vascular headache to a program of aerobic exercise training. Repeated measures of exercise behavior were examined through the use of a bidirectional changing criterion design. Repeated measures of headache activity were also collected. Results demonstrated a functional relationship between the behavioral package and exercise adherence, because all 5 subjects showed exercise behavior that matched bidirectional changing exercise criteria. The results also indicated clinically significant collateral reductions in vascular headache activity in 4 subjects. Subjects whose aerobic fitness levels were not masked by vasoactive medication also showed measurable increases in aerobic fitness. The results are discussed in terms of the methodology used to demonstrate a functional relationship between the adherence package and exercise behavior and the possible mechanism(s) by which aerobic exercise activity might affect vascular headache activity.